Numerical study on water distribution of natural draft wet cooling towers under crosswind - Guanghui BAI; Hao CHANG; Wei LI; Yongji CHEN; Guojun LI (Mechanical Engineering Journal, 2022)
In order to improve the thermal performance of natural draft wet cooling tower under crosswind, a three-dimensional numerical model for heat and mass transfer of cooling towers was established. The comparison with the design parameters of the cooling tower shows that this model satisfies the requirements of the thermal performance computation of cooling tower. According to the numerical calculation of the cooling tower and the analysis of the temperature, humidity and velocity field under various crosswinds velocities, a scheme of partition water distribution of cooling tower was proposed to deal with the effect of crosswind. Using this scheme, the influence of various spray water density ratio k on the thermal performance of cooling tower were researched, and the results show that the heat transfer performance of the cooling tower can be effectively improved under a certain comparing with uniform water distribution. When the cross wind speed is in the range of 2-6 m/s and this partition water distribution scheme is applied, maximum reduction of the outlet water temperature will reach 1.01K comparing with uniform water distribution.